Canteen food healthy tuckshops in our school - Brentnall, Kirrilly; Video Education Australasia (Bendigo, Vic. : Video Education Australasia, 2003)
This is the program to get the whole talking about the most important of school facilities: the canteen. It examines the importance of developing healthy eating habits at a young age and the role of the school canteen can play in encouraging students to eat nutritious food
Title from title screen
Executive producer, Mark McAuliffe ; editor, Joel De Courcy Browne ; camera & sound, Kieran Doolan, Shannon Sleeth
Presenter: Reeni Ekanayake
Keywords: School lunchrooms, cafetarias, etc; Food; School children -- Food